2016
DOI: 10.1097/sla.0000000000001394
|View full text |Cite
|
Sign up to set email alerts
|

A Risk Model and Cost Analysis of Incisional Hernia After Elective, Abdominal Surgery Based Upon 12,373 Cases

Abstract: Objectives:Incisional hernia (IH) remains a common, highly morbid, and costly complication. Modest progress has been realized in surgical technique and mesh technology; however, few advances have been achieved toward understanding risk and prevention. In light of the increasing emphasis on prevention in today's health care environment and the billions in costs for surgically treated IH, greater focus on predictive risk models is needed.Methods:All patients undergoing gastrointestinal or gynecologic procedures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(77 citation statements)
references
References 43 publications
4
73
0
Order By: Relevance
“…Our HERNIAscore models remain important scoring systems because they are among the few, if not only, models to include only preoperative and easily predictable intraoperative factors. Other scoring systems evaluate additional preoperative factors (chemotherapy, age, gender, thickness of subcutaneous fat, malnutrition, tobacco use, liver disease, ostomy reversal, acute gastrointestinal inflammatory process), operative factors (wound class, blood transfusion, suture type, continuous versus interrupted suture), and postoperative factors (surgical site infection) (1, 2, 4, 6, 7). These other scoring systems either use variables that are difficult to obtain or variables that cannot be easily determined prior to the operation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our HERNIAscore models remain important scoring systems because they are among the few, if not only, models to include only preoperative and easily predictable intraoperative factors. Other scoring systems evaluate additional preoperative factors (chemotherapy, age, gender, thickness of subcutaneous fat, malnutrition, tobacco use, liver disease, ostomy reversal, acute gastrointestinal inflammatory process), operative factors (wound class, blood transfusion, suture type, continuous versus interrupted suture), and postoperative factors (surgical site infection) (1, 2, 4, 6, 7). These other scoring systems either use variables that are difficult to obtain or variables that cannot be easily determined prior to the operation.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of models, however, use post-operative variables that limit their use for patient counseling and in implementing pre-operative or intra-operative interventions (1, 2, 4, 5, 6, 7). The HERNIAscore is a VIH risk assessment tool that utilizes only preoperative variables and predictable intra-operative variables: body mass index (BMI), chronic obstructive pulmonary disease (COPD), and incision length (laparoscopic, extended laparoscopy, or laparotomy) (8).…”
Section: Introductionmentioning
confidence: 99%
“…Incisional hernias carry a significant burden for both patients and the health service. They prevent return to normal activities and can be painful.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, due to the extra-adipose tissue in the subcuticular space, obese patiens are prone to develop seromas that often become infected because of the suboptimal vascularization of the adipose tissue [27][28][29][30]. In addition, obese patients require longer incisions and their surgeries are, most of the time longer with subsequent increased risk of tissue dissication and intraoperative contamination [1] that are predisposing factors for incisional hernias [31]. suggested that the lower rate of SSIs observed with the minimally invasive approach was due to the fact that the classical suprainguinal incision located in a highly colonized skin area was replaced with a 7 cm periumbilical incision that was much smaller and located in a more favorable area of the abdominal wall.…”
Section: Wound Complications In Obese Patientsmentioning
confidence: 99%